The Beginnings of Market Research and Measurement of Market Advertising Effectiveness - Dušan Pavlů (Communication Today, 2025)
Our academic literature about the history of Czech and Slovak advertising has been sketchy at best, often written under the influence of impressions rather than based on a real scientific analysis of historic reality, facts and development tendencies; in many cases it lacks thorough knowledge on the background of advertising, i.e. on the socio-economic, media, cultural, and creative environment in general. This study intends to analyse the beginnings of objectivization of analyses reflecting on the conditions for effective advertising at the turn of the 19th and 20th century, i.e. on the stages of development from the first dictionary definitions of the concept in 1868 up to the year 1927. It comes out of the contemporary local books, particularly, dictionary compendia – Slovník náučný (in English The Rigger’s Dictionary) published in 1868 and Ottův slovník naučný: ilustrovaná encyklopedie obecných vědomostí (In English The Otto´s Dictionary) in 1904. The author studies in detail two key books – monographs written by Zdenko Šindler (Moderní reklama, in English Modern Advertising, published in 1906), and by Vojta Holman (Reklama a život, i.e. Advertising and Life published in 1909) – and by doing so concentrates on their concept of an effective advertising activity. However, most attention is paid to Jan Brabec and his book published in 1927 under the title Zásady výnosné obchodní reklamy – na základě amerických studií a zkušeností, i.e. in English The Principles of Profitable Commercial Advertising – On the Basis of American Studies and Experience.1 The study comes to the conclusion that this book published by Jan Brabec actually laid the foundations for building a scientific theory associated with a specific communication activity, i.e. with the Czech advertising.